Laporan Kasus : Multipel Kolelitiasis dan Kolesistitis Akut Moderat pada Laki-Laki 68 Tahun dengan Hipertensi Kronis - Aswan, Naufal Rasyid; Wintoko, Risal (CV. Jasa Sukses Abadi, 2025)
Kolelitiasis (gallstones) is the deposition of crystals in the pacifier sac or in the pacifier duct, consisting of cholesterol, bilirubin, and pacifier. Although often asymptomatic and found incidentally, gallstones can cause right upper abdominal pain, nausea, vomiting, obstruction, cholangitis, and pancreatitis, especially after consuming oily or spicy foods. Obstruction of the cystic duct, either by stones or functional problems, can cause acute inflammation of the gallbladder (cholecystitis). Typical symptoms are usually biliary colic, including post-meal cramping pain in the right upper quadrant or epigastric pain radiating to the back or scapula, especially seen after eating high spicy foods, often accompanied by nausea and vomiting, while typical symptoms of cholecystitis are pain that does not go away, and a palpable mass in the right upper quadrant, causing congestion that is edematous and thickened. This disease occurs due to an imbalance involving lipids and bile salts in the bile stored in the gallbladder. Patient Mr. I, aged 68 years old have several risk factors and comorbid associated with Kolelitiasis and cholecystitis and the following case report presents a discussion of the patient's clinical features and laboratory test results related to the onset of this disease. The management given to this patient is operative management (Laparoscopic Cholecystectomy), drug management (analgesics), and non-drug management (education on lifestyle changes).